Common Atrium: A Rare Cause of Acute Decompensated Heart Failure - K. M. Karaye; S. A. Balarabe; M. M. Yakasai; I. M. Suleiman; H. Saidu; Aimé Bonny (Case Reports in Medicine)
We report a rare case of common atrium and acute decompensated heart failure most likely precipitated by acute bacterial pericarditis leading to premature death, in a 25-year-old male footballer. The silent course of the disease for decades as well as the diagnostic and management pitfalls of this case illustrates the importance of early detection by echocardiography and urgent appropriate treatment in intensive care settings to limit the poor prognosis of the condition.